Pendampingan Usaha Produk Lumpia Ubi Manis Mahasiswa Universitas Kristen Indonesia Toraja - Winta Panimba; Agner Polang; Yensinta Puspita Sari; Stepania Bandaso; Serafika Elyasiabela Sapan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The implementation of this service activity is carried out by providing material on Proposal Preparation and Food Business Planning for Sweet Potato Spring Roll Products by delivering this training material with lectures and discussions. Assistance is carried out to provide direction on how to start Business Planning and Preparing Business Proposals to Marketing and Business Development. The purpose of this assistance is to provide understanding and ability to students in starting a business well